Characterization of the Thermal, Structural, and Mechanical Properties of Recycled HDPE. Issue 1 (21st October 2022) - Chrysafi, Iouliana; Asimakidou, Theopoula; Michailidou, Georgia; Xanthopoulou, Eleftheria; Tziamtzi, Christina Kyriakou; Zamboulis, Alexandra; Bikiaris, Dimitrios N.
Abstract: High‐density polyethylene (HDPE) is one of the most popular plastics used in industry. Although it replaces many natural resources, due to the low cost and easy processing, its ever‐increasing wastes make it harmful for the environment. Thus, many processes are used in order to recycle it. In the present study, the properties of recycled HDPE (r‐HDPE) compared to virgin HDPE are investigated. The structural studies are performed by X‐ray diffraction (XRD). The thermal properties of virgin HDPE and r‐HDPE are measured by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Moreover, the mechanical properties are examined by Instron tensile strength experiments. Comparing the results, r‐HDPE does not show any significant differences regarding its structural and thermal properties. Additionally, it is found that r‐HDPE has a slight increase in tensile strength. As a result, considering that the mechanical process to produce r‐HDPE does not affect its general properties, it is suitable for further processing.